Machining GX2CrNiMoN26-7-4 DSS Alloy: Wear Analysis of TiAlN and TiCN/Al2O3/TiN Coated Carbide Tools Behavior in Rough End Milling Operations - Silva, Francisco (2020)
In the last decade, it has been common to observe a competition between coatings achieved via physical vapor deposition (PVD) and chemical vapor deposition (CVD) techniques on cutting tools used in machining processes. The tool’s substrate material can immediately condition the coating process selection. However, there are also materials capabe of adapting to any of the coating processes. Hence, the capabilities demonstrated by a given coating when created with one technique or another are usually different due to the intrinsic characteristics of each coating process, such as temperature and stress levels. In this work, to study the machining behavior of a super duplex stainless steel, PVD- and CVD-coated tungsten carbide inserts with different coatings were used in order to identify the wear mechanisms that affect each of the coatings and the workpiece’s surface quality, evaluated through different roughness parameters. The vibration level produced throughout the various tests was also registered in an attempt to associate the type of coating or insert failure with the level of vibrations generated in the CNC (Computer Numeric Control) machining spindle. This allowed us to conclude that the tools coated with TiAlN via PVD showed better wear behavior, as well as creating workpiece surfaces with less roughness. Thus, it was clear that this coating presents strong advantages in the machining of the super duplex stainless steel chosen for this work, being an innovative work due to the combination of materials used and the approach in terms of vibration analysis applied to milling